Prevalence of loneliness and social isolation among older adults during the COVID-19 pandemic: A systematic review and meta-analysis - Su, Yingying; Rao, Wenwang; Li, Muzi; Caron, Gabriel; D’Arcy, Carl; Meng, Xiangfei (International psychogeriatrics, 2023)
ABSTRACTObjectivesPandemics and their public health control measures have generally substantially increased the level of loneliness and social isolation in the general population. Because of the circumstances of aging, older adults are more likely to experience social isolation and loneliness during pandemics. However, no systematic review has been conducted or published on the prevalence of loneliness and/or social isolation among the older population. This systematic review and meta-analysis aims to provide up-to-date pooled estimates of the prevalence of social isolation and loneliness among older adults during the COVID-19 pandemic and other pandemics in the last two decades. DesignEMBASE, PsychoINFO, Medline, and Web of Science were searched for relevant studies from January 1, 2000 to November 31, 2021 published in a variety of languages. Only studies conducted during the COVID-19 pandemic were selected in the review. ResultsA total of 30 studies including 28,050 participants met the inclusion criteria. Overall, the pooled period prevalence of loneliness among older adults was 28.6% (95% CI: 22.9–35.0%) and 31.2% for social isolation (95% CI: 20.2–44.9%). Prevalence estimates were significantly higher for those studies conducted post 3-month from the start of the COVID-19 pandemic compared to those conducted within the first 3 months of the pandemic. ConclusionsThis review identifies the need for good quality longitudinal studies to examine the long-term impact of pandemics on loneliness and social isolation among older populations. Health policymaking and healthcare systems should proactively address the rising demand for appropriate psychological services among older adults.